2016
DOI: 10.1007/s00167-016-4188-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct versus indirect ACL femoral attachment fibres and their implications on ACL graft placement

Abstract: The centre of the ACL femoral attachment consisted of a direct fibre structure, while the posterior portion had an indirect fibre structure. These results support previous animal studies reporting that the centre of the ACL femoral insertion was comprised of the strongest reported fibre type. Clinically, the femoral ACL reconstruction tunnel should be oriented to cover the entirety of the central direct ACL fibres and may need to be customized based on graft type and the fixation device used during surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The differentiation between the two types of ligament insertions into the bone (direct and indirect) has been addressed by several other recent studies. 8 , 9 , 10 , 15 Studies that assessed the ACL demonstrated that the direct insertion, located predominantly in the most central portion of the ligament, played an important role in the mechanical attachment of the ligament to the bone, in contrast to the indirect insertion. 15 , 16 Uncalcified fibrocartilage, present only between the structural layers of the direct insertion, plays an important role in controlling the tension that occurs over the ligament, compatible with that observed in muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The differentiation between the two types of ligament insertions into the bone (direct and indirect) has been addressed by several other recent studies. 8 , 9 , 10 , 15 Studies that assessed the ACL demonstrated that the direct insertion, located predominantly in the most central portion of the ligament, played an important role in the mechanical attachment of the ligament to the bone, in contrast to the indirect insertion. 15 , 16 Uncalcified fibrocartilage, present only between the structural layers of the direct insertion, plays an important role in controlling the tension that occurs over the ligament, compatible with that observed in muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…From a microscopic standpoint, the insertion of the ligament to the bone has two distinct structures: direct and indirect insertion. 8 , 9 , 10 , 11 These two types of insertion are histologically different. While direct insertion has four histological layers (ligament, non-calcified fibrocartilage, calcified fibrocartilage, and bone), the indirect insertion presents only two (the ligament is inserted directly into the bone, without a clear transition between them).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus conversely, it is possible that the strong AM bundle tibial insertion renders the femoral origin more prone to injuries. Moulton et al () have shown that the ACL femoral enthesis contains a mixture of indirect and direct insertions and Beaulieu et al, () have found systematic reginal differences in collagen fibre attachment angles, however detailed microstructural characterization of the enthesis, especially data regarding to the interdigitation depth and frequency is still lacking. These counter arguments and knowledge gaps present scope for further investigation into the multi‐scalar structural realties of the ACL in relation to its vulnerability to injury.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical and biomechanical results have shown that the (functional) double-bundle or fanlike shape of a graft tends to more closely restore normal ACL function. 8 Owing to a lower revision rate, reduced graft elongation, and better return to the preinjury level of activity in earlier studies, the BPTB graft plays an important role especially in the young and active patient. 3,[9][10][11]…”
Section: Graft Choicementioning
confidence: 99%